2022
DOI: 10.3389/fvets.2022.953021
|View full text |Cite
|
Sign up to set email alerts
|

Temperature limits for storage of extended boar semen from the perspective of the sperm's energy status

Abstract: The optimum storage temperature for liquid-preserved boar semen has been empirically determined to be between 15 and 20°C. Lower temperatures provide an advantage to inhibit bacterial growth, but are regarded as critical due to the high sensitivity of boar spermatozoa to chilling injury. Higher storage temperatures are supposed to induce energy deficiency due to an insufficient depression of metabolic cell activity. However, experimental evidence for alterations of the sperm's energy status in relation to stor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Lipid architecture and the fluidity of the sperm plasma membrane can be altered by temperature changes [37,38], resulting in damage to sperm quality and functionality. Therefore, storage temperature at 17-25 • C is recommended for boar semen [39] because sperm quality loss is observed at >20 • C or <15 • C [40]. The results of this study indicate that post-thaw storage at 17 • C leads to better sperm quality than that at 5 • C and 37 • C. Accordingly, lower levels of apoptotic changes in boar sperm were observed at 17 • C in comparison with those at 5 • C and 37 • C, which could explain the results.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid architecture and the fluidity of the sperm plasma membrane can be altered by temperature changes [37,38], resulting in damage to sperm quality and functionality. Therefore, storage temperature at 17-25 • C is recommended for boar semen [39] because sperm quality loss is observed at >20 • C or <15 • C [40]. The results of this study indicate that post-thaw storage at 17 • C leads to better sperm quality than that at 5 • C and 37 • C. Accordingly, lower levels of apoptotic changes in boar sperm were observed at 17 • C in comparison with those at 5 • C and 37 • C, which could explain the results.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on in vitro semen storage in various species have indicated that sperm mitochondria experience failure under low temperature conditions, leading to reduced sperm fertilizability during storage 22 , 25 , 26 , 49 . Nevertheless, in mechanistic terms, our understanding of how sperm metabolism during cold storage relates to impaired fertility remains limited.…”
Section: Discussionmentioning
confidence: 99%
“…Sperm mitochondria play a vital role in coordinating ATP production, redox equilibrium, and calcium homeostasis, all of which can contribute to the regulation of sperm fertilization potential. Indicating a cross-genera conserved relevance, events that may be connected to mitochondrial impairments such as increased [Ca 2+ ] i levels, accumulation of reactive oxygen species (ROS), and decrease in mitochondrial membrane potential (ΔΨ M ) have been demonstrated to occur in the early stages of both liquid storage in chicken 20 , 21 and boar 22 , 23 semen. Nevertheless, specific mechanistic associations between increased [Ca 2+ ] i levels and reduced semen quality during storage or impact on mitochondrial function remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to short-term semen extenders, long-term preservation media usually provide higher sperm protection against different stressors like temperature fluctuation (29,30) or long-term exposure of seminal plasma during semen storage (31). Furthermore, they may also protect sperm better from bacterial stress, for example, caused by bacterial secretions (32) or binding to glycoprotein receptors on the sperm surface (33).…”
Section: Discussionmentioning
confidence: 99%